Empowerment Model of Micro, Small, and Medium Enterprises at Dinas Koperasi aan UKM Kabupaten Bandung - Nurochman, Raden Maman; Purwanto, Bambang Heru; Suyatna, Uyat (Ridwan Institute, 2025)
Micro-enterprises in Bandung Regency face systemic challenges, including limited capital access, fragmented empowerment programs, and weak post-training monitoring. Despite efforts by the Cooperatives and SMEs Office (DISKOP-UKM), gaps persist in achieving sustainable outcomes. This study evaluates DISKOP-UKM’s empowerment model, identifies implementation barriers, and proposes an enhanced framework integrating multi-stakeholder collaboration and digital solutions. A qualitative case study approach was employed, analyzing data from interviews, field observations, and DISKOP-UKM documents (2023–2025). Thematic analysis aligned findings with Chambers’ (1995) empowerment elements: people-centered, participatory, empowering, and sustainable. Current programs lack post-empowerment tracking and proactive stakeholder engagement. Successful interventions (e.g., Kopontren’s community-based model) highlight the potential of penta-helix collaboration and digital tools for scalability. The study recommends (1) adopting A-B-C-G-M partnerships to expand resources, (2) developing digital monitoring systems, and (3) diversifying capital access. These strategies address systemic inefficiencies and align with regional development goals, offering a replicable model for similar contexts.